2021
DOI: 10.1016/j.biochi.2021.09.009
|View full text |Cite
|
Sign up to set email alerts
|

On the footsteps of Hippocrates, Sanctorius and Harvey to better understand the influence of cold on the occurrence of COVID-19 in European countries in 2020

Abstract: COVID-19 pandemic has been characterized by a pattern of consecutive declines and regrowth in European countries in 2020. After being partially regressed during the summer, the reappearance of the infection during fall 2020 in many temperate countries strongly suggests that temperature and cold may play a role in influencing the infectivity and virulence of SARS-CoV-2. While promoting medicine as an art, Hippocrates interpreted with logical reasoning the occurrence of diseases such as epidemics, as a consequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 84 publications
0
3
0
Order By: Relevance
“…During reperfusion after ischaemia, reactive oxygen species can cause a series of destructive cell responses, inflammation, and cell damage, resulting in hepatic sinusoidal endothelial cell damage, and this microcirculation disorder further aggravates hepatic ischaemia and hypoxia, thereby aggravating liver damage and creating a vicious cycle. Notably, cold accelerates the constriction of blood vessels, especially microvessels, which exacerbates inflammatory responses by inducing hypoxia and stimulating aerobic glycolysis in cells [8] .…”
Section: Microvascular Thrombosis and Hepatic Ischaemiareperfusion In...mentioning
confidence: 99%
See 1 more Smart Citation
“…During reperfusion after ischaemia, reactive oxygen species can cause a series of destructive cell responses, inflammation, and cell damage, resulting in hepatic sinusoidal endothelial cell damage, and this microcirculation disorder further aggravates hepatic ischaemia and hypoxia, thereby aggravating liver damage and creating a vicious cycle. Notably, cold accelerates the constriction of blood vessels, especially microvessels, which exacerbates inflammatory responses by inducing hypoxia and stimulating aerobic glycolysis in cells [8] .…”
Section: Microvascular Thrombosis and Hepatic Ischaemiareperfusion In...mentioning
confidence: 99%
“…Studies have shown that temperature may affect the infectivity and virulence of SARS-CoV-2, and a cold environment is conducive to the duplication and spread of the virus [8] . Determining the possible mechanisms and causes of liver injury is critical for making clinical decisions for the therapeutic management of COVID-19 in cold regions.…”
Section: Introductionmentioning
confidence: 99%
“…The high immunity of the population despite the spread of the Delta variant led to the suppression of the spread of SARS-CoV-2 in general [16]. However, over time, the weakening of post-infectious immunity, increasing mobility of the population and the approach of the winter period in which the pattern of human contact changes, the Delta strain has aggravated the epidemic situation [18].…”
Section: Issn 1728-3817mentioning
confidence: 99%